Hydrothermal synthesis of cobalt telluride nanorods for a high performance hybrid asymmetric supercapacitor. Issue 23 (3rd April 2020) - Manikandan, M.; Subramani, K.; Sathish, M.; Dhanuskodi, S.
Abstract : A one-step hydrothermal derived cobalt telluride nanorods and activated carbon-based hybrid asymmetric supercapacitor delivered a high energy (40.7 W h kg −1 ) and power density (22.5 kW kg −1 ) with an electrochemical stability of 85% for 10000 cycles. Abstract : Cobalt telluride nanostructured materials have demonstrated various applications, particularly in energy generation and storage. A high temperature and reducing atmosphere are required for the preparation of cobalt telluride-based materials, which makes this a difficult and expensive process. The development of a facile route for producing the desirable nanostructure of cobalt telluride remains a great challenge. We demonstrated a simple hydrothermal method for preparing cobalt telluride nanorods (CoTe NRs) and telluride nanorods (Te NRs) for supercapacitor applications. The morphology of CoTe NRs and Te NRs was analyzed using scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The prepared CoTe NR electrode material exhibited a high specific capacity of 170 C g −1 at a current density of 0.5 A g −1 with an exceptional cyclic stability. The asymmetric supercapacitor was assembled using CoTe NRs and orange peel-derived activated carbon (OPAA-700) as a positive and negative electrode, respectively. The fabricated device delivered a high energy density of 40.7 W h kg −1 with a power density of 800 W kg −1 at 1 A g −1 current density. When the current density was increased to 30 A g −1, the fabricated device delivered a high power density of 22.5 kW kg −1 with an energy density of 16.3 W h kg −1 . The fabricated asymmetric supercapacitor displayed a good cyclic stability performance for 10 000 cycles at a high current density of 30 A g −1 and retained 85% of its initial capacity for after 10 000 cycles. The prepared materials indicate their applicability for high performance energy storage devices.